2018
DOI: 10.3892/ijmm.2018.3498
|View full text |Cite
|
Sign up to set email alerts
|

AMP-activated protein kinase stimulates osteoblast differentiation and mineralization through autophagy induction

Abstract: Previous studies have reported that adenosine mono-phosphate-activated protein kinase (AMPK) activation can enhance osteoblast differentiation and mineralization; however, the underlying mechanism is not fully understood. Autophagy also serves an important role in osteoblast mineralization and bone homeostasis. The present study aimed to explore whether activation of AMPK could enhance osteoblast differentiation and mineralization via the induction of autophagy. The fracture healing and nonunion animal models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 47 publications
1
57
0
Order By: Relevance
“…Autophagy has been suggested to regulate bone homeostasis by modulating osteoblast differentiation and mineralization, as well as adjusting osteoclast differentiation and function ( 12 , 13 ). Recent studies have reported the cytoprotective effects of autophagy on osteoblast survival, differentiation and mineralization ( 13 15 ). However, it is currently unclear whether radiological stress-induced autophagy is actually cytoprotective and which molecular mechanisms are involved.…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy has been suggested to regulate bone homeostasis by modulating osteoblast differentiation and mineralization, as well as adjusting osteoclast differentiation and function ( 12 , 13 ). Recent studies have reported the cytoprotective effects of autophagy on osteoblast survival, differentiation and mineralization ( 13 15 ). However, it is currently unclear whether radiological stress-induced autophagy is actually cytoprotective and which molecular mechanisms are involved.…”
Section: Introductionmentioning
confidence: 99%
“…All of these effects by metformin seem to be related to its action as an The molecular mechanism underlying the role of AMPK activation in osteogenic differentiation and bone regeneration remains unclear. AMPK activation may promote bone formation by enhancing autophagy [42]. AMPK controls the osteogenic differentiation of human MSCs through early mTOR inhibition-mediated autophagy and late activation of the Akt/mTOR signaling axis [43].On the other hand, as a direct substrate of AMPK, RUNX2 can stimulate osteoblast differentiation and bone formation [44].…”
Section: Discussionmentioning
confidence: 99%
“…(OCN), RUNX2 expression and the induction of mammalian target of rapamycin (mTOR)-mediated autophagy ( Figure 1) (Pantovic et al, 2013;Li et al, 2018a). Furthermore, hormones (e.g., melatonin and ecdysterone), promote osteogenesis by mediating the AMPKα (Thr172)/β-catenin signalling pathway in different osteoblastic cells, which inhibits osteoclast differentiation and function (Xu et al, 2017;Jiang et al, 2019).…”
Section: Figure 1 Model For the Activation Of Ampk During Osteoclast mentioning
confidence: 99%